The Approach of Missing and Abducted Children Cases in Turkey: Criticism of First Response, Criminal Investigation and TV Programs - Gönültaş, Burak Miraç; Edges, Charlie (The Bulletin of Legal Medicine, 2021)
Objective:  The present study try to criticise how to approach and intervene in cases of missing children in Turkey in the context of first response, criminal investigation and TV Programmes, thus to offer suggestions on how to make more effective interventions in missing children cases.Methods: The research adopted a qualitative analysis method and in order to collect data, interviewing and documenting technic from professionals related to Turkish approach (n=5), and speakers and producers of TV programmes (ATV-Sweet Hard and Fox TV- Missing Flowers) related to missing children (n=3) were applied. Then collected data were analysed.Results: In Turkey, missing cases are investigated in terms of judicial and administrative tasks of police. Search teams, helicopters, lost dogs are used in search studies. When the police learn about the missing case, they conduct field work first, and if there is a sign of abduction, investigative teams are included. TV programs are especially effective in reaching large audiences in child's search studies. Thus, potential eyewitnesses can be reached. Besides, there are inadequency in terms of risk assessment, coordination and psychosocial backup for families.Conclusion: In relation to the components of missing children cases, Turkey should improve their approach about risk assessment, coordinators and supervising professionals and utilization of the media. The study also reveals the requirements of a general framework for missing children investigations.
Keywords: missing child; abducted child; Turkey; risk assessment; criminal investigation